Unusual biogenic calcite structures in two shallow lakes, James Ross Island, Antarctica - Elster, J. (Josef); Nedbalová, L. (Linda); Vodrážka, R.; Láska, K.; Haloda, J.; Komárek, J. (Jiří) (Biogeosciences, 2016)
The floors of two shallow endorheic lakes, located on volcanic surfaces on James Ross Island, are covered with calcareous organosedimentary structures. Their biological and chemical composition, lake water characteristics, and seasonal variability of the thermal regime are introduced. The lakes are frozen down to the bottom for 8– 9 months a year and their water chemistry is characterised by low conductivity and neutral to slightly alkaline pH. The photosynthetic microbial mat is composed of ilamentous cyanobacteria and microalgae that are considered to be Antarctic endemic species.